2007
DOI: 10.1038/sj.onc.1210443
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant FoxM1B expression increases matrix metalloproteinase-2 transcription and enhances the invasion of glioma cells

Abstract: We recently showed that FoxM1 is overexpressed in human glioblastomas and that forced FoxM1B expression in anaplastic astrocytoma cells leads to the formation of highly invasive glioblastoma multiforme (GBM) in nude mice. However, the molecular mechanisms by which FoxM1 enhances glioma invasion are unknown. In this study, we found that FoxM1 overexpression increased matrix metalloproteinase (MMP)-2 expression in glioma cells, whereas blockade of FoxM1 expression suppressed MMP-2 expression. Transfection of Fox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
148
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(162 citation statements)
references
References 28 publications
(39 reference statements)
14
148
0
Order By: Relevance
“…Another report showed that MMP2 transcription was directly upregulated by FoxM1 and that the invasion of glioma cells was enhanced by FoxM1-induced MMP2 expression (30). In the present study, MMP2 expression was markedly decreased in FoxM1-knockdown cells (Fig.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Another report showed that MMP2 transcription was directly upregulated by FoxM1 and that the invasion of glioma cells was enhanced by FoxM1-induced MMP2 expression (30). In the present study, MMP2 expression was markedly decreased in FoxM1-knockdown cells (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…However, FoxM1 also promotes the MMP2 expression that is associated with enhanced invasion by glioma cells (30). On the basis of the available evidence, we hypothesized that MnSOD might upregulate FoxM1 transcription, thereby promoting tumor aggressiveness via increased MMP2 expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, characteristic features of malignant glioma are its elevated cell motility and invasion which are currently known to be regulated by various molecules such as extracellular matrix, integrins, matrix metalloproteinases, growth factor receptors, focal adhesion kinases, PI-3 kinase, small GTPase, and transcription factors [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The elevated expression of the MMP-2 immunoreactive protein is correlated with a poor prognosis in OCSCC (Ruokolainen et al, 2004;Gao et al, 2005;Patel et al, 2007). In addition, MMP-2 expression could be regulated by several transcription factors, including YB-1 (Mertens et al, 1997), Sp1 (Qin et al, 1999), p53 (Bian and Sun, 1997), Stat3 (Xie et al, 2004) and FOXM1 (Dai et al, 2007); however, the molecular mechanisms by which MMP-2 is activated and controls tumor metastasis in OCSCC remain elusive.…”
Section: Introductionmentioning
confidence: 99%